2017
DOI: 10.1111/all.13362
|View full text |Cite
|
Sign up to set email alerts
|

RCAT reflects symptom control and quality of life in allergic rhinoconjunctivitis patients

Abstract: The strong correlations suggest that the RCAT alone is equivalent to the RQLQ with respect to patients' symptom control and quality of life. Patients with uncontrolled symptoms can be identified using the RCAT. Hence, the physician can decide whether symptomatic therapy can be intensified or allergy immunotherapy should be administered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…In addition, cross‐reactivity of birch pollen allergens extends to plant food allergens, resulting in the pollen food syndrome (PFS) . Subsequently, the negative impact on health‐related quality of life in patients allergic to birch pollen is substantial . The purpose of this manuscript was to narratively review topics of interest such as taxonomy, cross‐reactivity, prevalence, PFS, and quality of life with regard to birch pollen allergy from a European perspective.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, cross‐reactivity of birch pollen allergens extends to plant food allergens, resulting in the pollen food syndrome (PFS) . Subsequently, the negative impact on health‐related quality of life in patients allergic to birch pollen is substantial . The purpose of this manuscript was to narratively review topics of interest such as taxonomy, cross‐reactivity, prevalence, PFS, and quality of life with regard to birch pollen allergy from a European perspective.…”
Section: Introductionmentioning
confidence: 99%
“…One published study that evaluated HRQoL in patients specifically allergic to birch pollen simply reported that there was no difference in HRQoL between monosensitized and polysensitized (defined as sensitization to at least 2 allergens among Bet v 1, Bet v 2, and Bet v 4) patients . Using the Rhinitis Control Assessment Test, another study found that 45.7% of patients with birch pollen allergy who were receiving treatment in accordance with Allergic Rhinitis and its Impact on Asthma recommendations had insufficiently controlled symptoms . More research is needed to determine the impact of birch allergy specifically on HRQoL, as well as the socioeconomic burden of disease.…”
Section: Introductionmentioning
confidence: 99%
“…Even with the most effective intranasal formulation, combined azelastine and fluticasone furoate, patients with moderate-to-severe allergic rhinitis showed a relatively low responder rate of 12.4% [ 56 ] or 16.7% [ 57 ] after 14 days of treatment. In general, only 30.3% of grass pollen-allergic patients and 54.3% of those suffering from birch pollen allergy attain symptom control with guideline-concordant pharmacotherapy [ 58 ]. All studies investigating a monotherapy with ectoine invariably attested positive effects of ectoine monotherapy in alleviating symptoms of allergic rhinitis.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the percentage of patients who did not need any symptomatic medication increased by over 25% of the whole cohort in 2017 (in total 34.3%) compared to the previous season. Liedtke et al 19 . reported that patients who attained symptom control used significantly less symptomatic medication than did patients with uncontrolled symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…The German version of the validated Rhinitis Control Assessment Test (RCAT) 19 was used to determine whether patients' rhinitis symptoms were controlled in the peak of the 2017 pollen season (assessed prospectively at V4). The RCAT is based on six items: nasal congestion, sneezing, watery eyes, sleep disruption, and activity limitation caused by symptoms, as well as patients’ self-rating of symptom control.…”
Section: Methodsmentioning
confidence: 99%